One-dimensional TiO2 nanotubes arrays: Influence of anodisation voltage and their photocatalytic activity performance - Lee, W.H.; Lai, C.W.; Lim, Y.S.; Hamid, Sharifah Bee Abd (Taylor & Francis, 2014)
A systematic study of titanium dioxide (TiO2) nanotube arrays grown by electrochemical anodisation in an ethylene glycol electrolyte containing 0.5 wt-% ammonium fluoride has been carried out, with a range of anodisation voltage of 15-60 V for 1 hour. Among all of the applied anodisation voltages, 60 V resulted in the highest aspect ratio TiO2 nanotube arrays with the tube length of approximately 2 mu m and pore size of 105 nm. The diameter and length of nanotubes were found to be increased with anodisation voltage because of the high electric field dissolution at the barrier layer of nanotubes. Besides, the anatase phase of TiO2 could be detected from the X-ray diffraction patterns after subjecting the annealing process at 400 degrees C in argon atmosphere for 4 hours. Based on the photocatalytic studies, it was observed that TiO2 nanotube arrays with the highest aspect ratio (length/pore's size) exhibited preferably high photocatalytic activity among the samples owing to the larger active surface area to generate more photo-induced electron-hole pairs. This condition will enhance the photocatalytic degradation efficiency of methyl orange.